Comparative analysis of zebrafish bone morphogenetic proteins 2, 4 and 16: molecular and evolutionary perspectives - Marques, Cátia L. (2016)
BMP2, BMP4 and BMP16 form a subfamily of bone morphogenetic proteins acting as pleiotropic growth factors during development and as bone inducers during osteogenesis. BMP16 is the most recent member of this subfamily and basic data regarding protein structure and function, and spatio-temporal gene expression is still scarce. In this work, insights on BMP16 were provided through the comparative analysis of structural and functional data for zebrafish BMP2a, BMP2b, BMP4 and BMP16 genes and proteins, determined from three-dimensional models, patterns of gene expression during development and in adult tissues, regulation by retinoic acid and capacity to activate BMP-signaling pathway. Structures of Bmp2a, Bmp2b, Bmp4 and Bmp16 were found to be remarkably similar; with residues involved in receptor binding being highly conserved. All proteins could activate the BMP-signaling pathway, suggesting that they share a common function. On the contrary, stage-and tissue-specific expression of bmp2, bmp4 and bmp16 suggested the genes might be differentially regulated (e.g. different transcription factors, enhancers and/or regulatory modules) but also that they are involved in distinct physiological processes, although with the same function. Retinoic acid, a morphogen known to interact with BMP-signaling during bone formation, was shown to downregulate the expression of bmp2, bmp4 and bmp16, although to different extents. Taxonomic and phylogenetic analyses indicated that bmp16 diverged before bmp2 and bmp4, is not restricted to teleost fish lineage as previously reported, and that it probably arose from a whole genomic duplication event that occurred early in vertebrate evolution and disappeared in various tetrapod lineages through independent events.